Feed Efficiency and Physiological Parameters of Holstein and Crossbred Holstein × Simmental Cows - Deise Aline Knob; Armin Manfred Scholz; Laiz Perazzoli; Bruna Paula Bergamaschi Mendes; Roberto Kappes; Dileta Regina Moro Alessio; Ângela Fonseca Rech; André Thaler Neto (Animals, 2023)
This study aimed to compare the feed efficiency (FE) and physiological parameters of Holstein and crossbred Holstein × Simmental cows in a confinement system during winter and summer. The study was conducted in a dairy farm in southern Brazil by including a total of 48 multiparous cows. The cows were studied for 21 days in two periods, summer and winter, and their daily dry matter intake (DMI), milk yield (MY), rectal temperature (RT), respiratory rate (RR), body weight, and body condition score were recorded. An analysis of variance was conducted using the SAS statistical package. The results showed that crossbred Holstein × Simmental cows have a similar FE as Holstein cows in a high-production system (1.83 × 1.81 kg DMI/kg MY, respectively), and they can achieve the same production levels as purebred Holstein cows (43.8 vs. 44.5 milk/cow/day). Our findings indicated a difference for the period as both genetic groups achieved higher FE in winter than in summer (1.98 vs. 1.67 DMI/kg MY, respectively). In addition, we found evidence that crossbred cows are better at dissipating body heat during heat-stress situations, as they have higher RR in summer compared to purebred cows, while Holstein cows have higher RT in summer afternoons than crossbred cows. Therefore, using crossbred Holstein × Simmental cows is an alternative for high-production systems.